2018
DOI: 10.1007/s00167-018-5253-3
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of symptomatic in-hospital VTEs in Asian patients undergoing joint arthroplasty was low: a prospective, multicenter, 17,660-patient-enrolled cohort study

Abstract: Purpose The aim of this study was to determine the real incidence of symptomatic in‐hospital venous thromboembolism (VTE) and identify risk factors for VTEs in Asian patients undergoing total hip (THA) and total knee arthroplasty (TKA). Methods A total of 17,660 patients (20,078 hips and knees) undergoing THA and TKA at 78 hospitals were enrolled. The composite incidence of symptomatic in‐hospital DVT and PE was identified as the primary effectiveness outcomes. The primary safety outcomes were the incidences o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 27 publications
4
20
0
Order By: Relevance
“…Studies have shown that reasonable use of anticoagulants can effectively reduce the incidence of VTE after hip and knee arthroplasty (38)(39)(40). However, inappropriate use of anticoagulants can increase the incidence of adverse events, such as infection, poor wound healing, and increased blood loss (27,41,42).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that reasonable use of anticoagulants can effectively reduce the incidence of VTE after hip and knee arthroplasty (38)(39)(40). However, inappropriate use of anticoagulants can increase the incidence of adverse events, such as infection, poor wound healing, and increased blood loss (27,41,42).…”
Section: Discussionmentioning
confidence: 99%
“…The rate of DVT after AKO was almost the intermediate value between TKA and ACLR; thus, our hypothesis was confirmed. The incidence of symptomatic VTEs in Asian regions is low in comparison to studies targeting Western populations [5].…”
Section: Discussionmentioning
confidence: 80%
“…Lee et al used the Korean National Health Insurance (NHI) claims database in 2010 to show a 90-day VTE rate of 3.8% (DVT 3.2%, PE 0.7%), which may be significantly higher than other studies because the rate of chemoprophylaxis was only 48.4% [ 40 ]. Zeng et al studied 78 hospitals in Asia between 2013–2016 and found an in-hospital DVT rate of 0.36%, which is much lower than rates in other studies [ 44 ].…”
Section: Rates Of Vte After Total Hip and Knee Arthroplastymentioning
confidence: 82%
“…Fuji et al used an administrative database of Japanese patients between 2008 and 2013, and found an overall VTE rate of 0.9% (DVT 0.9%, PE 0.2%) [ 43 ]. Zeng et al studied 78 hospitals in Asia between 2013–2016 and found an in-hospital DVT rate of 0.21% [ 44 ].…”
Section: Rates Of Vte After Total Hip and Knee Arthroplastymentioning
confidence: 99%
See 1 more Smart Citation